Effect of Blue Light–Reducing Eye Glasses on Critical Flicker Frequency. Issue 2 (March 2015) - Ide, Takeshi; Toda, Ikuko; Miki, Emiko; Tsubota, Kazuo
<x xml:space="preserve">Abstract</x> Purpose This study aims to evaluate the effect of blocking short-wavelength light on critical flicker frequency (CFF). Design This study is a prospective clinical study. Methods Thirty-three participants (17 men and 16 women; age range, 28–39 years) were divided into 3 groups. Each group wore 1 of 3 types of lenses while performing an intensive computer task for 2 hours. To evaluate the effect of blocking short-wavelength light before and after the task, we measured the CFF and evaluated subjective questionnaires. We used the analysis of variance test to examine whether the type of lenses tested affected any of the visual fatigue-related parameters. Results The type of lens worn significantly affected the CFF; however, answers to the subjective questionnaires did not differ significantly between the groups. Two of the 13 question items showed a statistical difference between lens transparency and increase in the CFF (lens 3 > lens 2 > lens 1). Conclusions The higher the blocking effect of the lens, the lower the reduction in the CFF, suggesting that blocking short-wavelength light can reduce eye fatigue.